1989
DOI: 10.1073/pnas.86.3.881
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of growth of nonbasal planes in ice by fish antifreezes.

Abstract: Peptide and glycopeptide antifreezes from a variety of cold-water fishes cause ice single crystals grown from the melt to assume unusual and strikingly similar habits. The antifreezes inhibit growth on the prism faces but allow limited growth on the basal plane. As new layers are deposited on the basal plane, pyramidal surfaces develop on the outside of the crystal, and large hexagonal pits form within the basal plane. The pits are rotated 30' with respect to the normal orientation of hexagonal ice crystals. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(96 citation statements)
references
References 26 publications
(27 reference statements)
7
88
1
Order By: Relevance
“…All the classical MD simulations were performed on the systems in canonical (NVT) ensemble with the GROMACS software package [32]. Following equilibration, trajectories of 2 ns were obtained at 300 K with a Nose-Hoover thermostat [22,23]. Nonbonded interactions were gradually brought to zero by a shift function for the electrostatics as well as a switch function for van der Waals interactions between 10 and 12Å [24,25].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the classical MD simulations were performed on the systems in canonical (NVT) ensemble with the GROMACS software package [32]. Following equilibration, trajectories of 2 ns were obtained at 300 K with a Nose-Hoover thermostat [22,23]. Nonbonded interactions were gradually brought to zero by a shift function for the electrostatics as well as a switch function for van der Waals interactions between 10 and 12Å [24,25].…”
Section: Methodsmentioning
confidence: 99%
“…The generally accepted mechanism for the Type I AFP is the adsorption-inhibition mechanism [22][23][24], which proposes that AFPs adsorb onto the preferred growth sites of an ice surface, thereby preventing new ice growth [25]. It was initially thought that ice and AFP interacted through hydrogen bonding [22].…”
Section: Introductionmentioning
confidence: 99%
“…This has been attributed to a secondary property of AF(G)Ps known as dynamic ice shaping (DIS), which is intrinsically linked to their TH property. Essentially, AF(G)Ps bind to specific planes of ice, inhibiting their growth, but upon cooling, the remaining exposed faces grow, giving rise to a spicular (needle-like) morphology causing mechanical damage 17 . Carpenter et al 11 and Matsumoto et al 18 demonstrated small improvements in cryopreservation with an AFP and an AF(G)P mimic respectively, but the benefit was limited by the low concentrations, which could be applied before cell viability was reduced because of ice-shaping.…”
mentioning
confidence: 99%
“…The data also revealed that the low molecular weight AFGP 6-8 are less active than the high molecular weight AFGP 1-5. Also, the thermograms of AFGP revealed an initial shoulder in the exotherm direction upon cooling which correlates with observed c-axis ice growth (Raymond et al 1989, Hansen et al 1991; and, the loss of the shoulder during annealing experiments represents the end of the ice growth.…”
Section: Discussionmentioning
confidence: 91%